Amyotrophic lateral sclerosis in seven provinces of Chinese mainland: A cross-sectional survey from 2015 to 2016 - Zhang, Jie; Liu, Xiaoqing; Liang, Huiting; Xu, Shengyuan; Wang, Xiaohua; Xu, Renshi (Frontiers in Aging Neuroscience, 2022)
Background The large-scale survey about amyotrophic lateral sclerosis (ALS) based on both population and hospitals in the Chinese mainland has been deficient at present. To this end, we conducted a cross-sectional survey about ALS based on the population and hospitals in seven provinces of the Chinese mainland in 2015–2016. Methods We surveyed patients with ALS in seven provinces in eastern, middle, and western China. Among them, 13 prefecture-level cities, 13 municipal districts, 13 counties, 26 streets, 52 communities, 39 towns, and 78 administrative villages were selected for the population-based survey. Totally, 13 class-3 general hospitals, 13 class-2 general hospitals, and 26 street health centers or community health service centers in urban districts, and 13 county-level general hospitals, 39 township health centers, and 78 village clinics in rural districts were recruited for the hospital-based survey. Results Among the Chinese mainland, the total prevalence of ALS was slightly lower than that of the world's other nations or districts. The male patients were more than female patients. The prevalence of rural residents was more than that of urban residents. The prevalence of farmers was higher than that of other professions. The majority of ALS was not accompanied by other chronic diseases. The peak onset age of ALS was higher, familial ALS (fALS) cases were slightly more, and the average survival duration of sporadic ALS (sALS) was slightly lower compared with the previous investigation data. The hospitalization expenses of almost 60% of ALS were not more than 10,000 Chinese Yuan. Conclusion Hospitalization expenses in our survey objectives were the lowest in the current reported countries and districts. A farmer was a possible higher risk profession for ALS, the majority of ALS were not accompanied by other chronic diseases. Our survey provided more information on the epidemiology of ALS worldwide and supplied the deficiency of epidemiology survey about ALS from the Chinese mainland.